Proliferating cell nuclear antigen expression in mucoepidermoid carcinoma of salivary glands - Cardoso, Weder Pereira; Denardin, Odilon Victor Porto; Rapoport, Abrão; Araújo, Vera Cavalcanti; Carvalho, Marcos Brasilino (São Paulo Medical Journal, 2000)
CONTEXT: Among the cytological and morphological properties of mucoepidermoid carcinoma, one of the most important criteria for measuring its biological behavior and aggressiveness is cell proliferation. In this way, immunohistochemical markers of cell proliferation have been found to be useful in tumor classification and have formed part of the prognostic and therapeutic studies of these pathologies. OBJECTIVE: To analyze 11 cases of mucoepidermoid carcinoma (MEC) using the proliferation activity marker (PCNA) and to determine its relationship to the grade of malignancy of these tumors. DESIGN: Correlation study. SETTING: Head and Neck Surgery Service of Heliópolis Hospital, São Paulo, Brazil. SAMPLE: Slides of 11 cases of primary mucoepidermoid carcinomas of salivary glands were prepared according to routine techniques employed in the Oral Pathology Department of the Dentistry Faculty of São Paulo University, Brazil. They were fixed in a 10% formaldehyde solution and stained with hematoxylin and eosin. After this preparation the tumors were classified as low, intermediate and high grade of malignancy, according to the criteria established by Seifert & Sobin and Auclair, Goode & Ellis. The slides were sent for immunohistochemical processing to evaluate the positivity of proliferating cell nuclear antigen using the streptavidin biotin technique. MAIN MEASUREMENT: The correlation between proliferating cell nuclear antigen expression and the histological malignancy grade in mucoepidermoid carcinoma of salivary glands. RESULTS: there were 4 cases (36%) of low grade, 4 cases (36%) of intermediate grade and 3 cases (27%) of high grade of malignancy. After a comparative study between histological features and immunohistochemical analysis, significant differences were observed (P < 0.01) for low, intermediate and high grades: 16.04%, 26.98% and 56.98% of proliferating cell nuclear antigen expression in mucoepidermoid carcinoma , respectively. CONCLUSION: The proliferating cell nuclear antigen expression increases with the grade of malignancy in mucoepidermoid carcinoma of salivary glands.